Esophagectomy for end‐stage achalasia. Issue 1 (8th July 2016) - Felix, Valter Nilton
Abstract : End‐stage achalasia is rarely effectively addressed with conservative treatments, as food must traverse a serpiginous route to reach the stomach. Botox injections in the setting of end‐stage achalasia will likely provide minimal temporary palliation at best, pneumatic dilation has higher risks of perforation, and laparoscopic myotomy, while minimally invasive, has presented poor results. Under these circumstances, there are many proposed procedures to restore a viable alimentary condition to patients, from partial to subtotal resection of the esophagus; each of procedures confers both advantages and specific risks. Subtotal esophagectomy must be indicated for end‐stage disease (tortuous or sigmoid esophagus) and persistent dysphagia after failed interventions. When performed by experienced hands, the procedure can be undertaken successfully, with acceptable postoperative morbidity and mortality, improvement of symptoms, and a good long‐term quality of life in the majority of patients.